Specificity of Garden and Park Topoi in Novellas of Theodor Storm - E. R. Kirdyanova (Научный диалог, 2025)
This article examines the artistic significance of garden and park topoi within the poetics of Theodor Storm's novellas. The author focuses on the characteristics of these elements concerning their aesthetic, structural, and semantic importance. As a complex phenomenon within the author's artistic world, gardens and parks embody the system of relationships between humanity, nature, and society. The relevance of this study is underscored by the introduction of contemporary approaches to analyzing park, garden, and estate topoi in the novellistic works of Theodor Storm, which reveal both universal and author-specific techniques for modeling these spaces. The aim of the research is to synthesize observations regarding the distinctive artistic representation of gardens and parks as unique spaces in Storm's novellas. It is noted that gardens, as integral components of literary works, function as a double text; on one hand, they serve as analogs of the real world, while on the other hand, they are intertwined with cultural traditions and their literary functions. The garden as a text within a text acquires new meanings that are interpreted through the author’s consciousness. It is emphasized that gardens represent a text that unites various arts and is subject to changing perceptions across different eras. The primary semantics of the garden topos is established as representing a unique moral and spiritual space. A notable characteristic of Storm's style is his focus on experiences and emotional states, often expressed through the lens of memory.